Macroeconomic News and Price Discovery in Indonesian Government Bond Market - Ervina, Dahlia (Information Management and Business Review, 2015)
The study of macroeconomic news impact on government bond gets little attention, especially in emerging markets. Andritzky et al. (2007) and Nowak et al. (2011) study this impact for some emerging countries, but little attention given to Asian countries. The question about whether macroeconomic news have impacts on government bond is important, considering the large amount of government bonds outstanding in Indonesia and the importance of regulation to maintain the stabilization of bond price. This research use daily returns of Indonesian government bond benchmark series over five-year period to investigate the impact of domestic and global macroeconomic news announcements. We study the relationship using event study approach. Following common literature we use surprise component of macroeconomic news announcements, which will be defined as the difference between market expectation and the actual release of the macroeconomic news. We use economic forecast survey conducted by Bloomberg as the proxy of market expectations needed to calculate domestic (Indonesia) and global (US) macroeconomic news announcements surprises. We find that, for bond returns, surprises of global macroeconomic news announcements is more important than domestic ones, especially for recent years, while both surprises of global and domestic macroeconomic news announcements affect bond returns volatility.